A Review Paper on Design and Experience of Mobile Applications - Durgekar, Sanket R; Rahman, Sayeed Abdul; Naik, Sharat R; Kanchan, Sharath S; Srinivasan, G (EAI Endorsed Transactions on Scalable Information Systems, 2024)
Development of mobile applications is becoming increasingly important as a field as a result of the proliferation of mobile devices. However, due to poor User Interface (UI) and User Experience (UX) , many apps struggle to hold the interest of their intended users. As a result, achieving user expectations is difficult for developers. Numerous facets of mobile application design and UX/UI have been examined. Yet, they often overlook critical factors such as context, user behavior, emotions, control, usability, adaptability, language, and feedback, instead favoring isolated issue-centric approaches Taking into account all of the aforementioned factors, This review gathered preferences and perceptions. These preferences offer vital information for mobile application developers and act as a useful reference. Based on the pertinent context, the method helps designers and developers to address certain UI/UX difficulties in mobile applications. The UI and UX elements that affect the interface of mobile applications are compared in this essay. Developers and designers can better comprehend crucial elements during the development process by looking at these criteria. This helps to improve the UI and UX of mobile applications, which ultimately boosts usability and user satisfaction.
Keywords: User Interface; User Experience; Mobile Application